2010
DOI: 10.1021/ac902456n
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of the Fluorescent Ribonucleotide Analogue tCTP by T7 RNA Polymerase

Abstract: Fluorescent RNA is an important analytical tool in medical diagnostics, RNA cytochemistry and RNA aptamer development. We have synthesized the fluorescent ribonucleotide analogue 1,3-diaza-2-oxophenothiazine-ribose-5′-triphosphate (tCTP) and tested it as substrate for T7 RNA polymerase in transcription reactions, a convenient route for generating RNA in vitro. When transcribing a guanine, T7 RNA polymerase incorporates tCTP with 2-fold higher catalytic efficiency than CTP and efficiently polymerizes additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 49 publications
4
45
0
Order By: Relevance
“…DinB synthesizes DNA up to and across from tC, accurately incorporating G, but cannot efficiently bypass tC. It has also been observed that tC can tautomerize to a form that base pairs with A; 41,42 however, similar to human DNA primase and RNA polymerase, 42,43 we did not observe misincorporation by DinB. The tC analog is known to be bypassed by the A-family polymerase Klenow fragment, as well as by human DNA polymerase α primase.…”
Section: Discussionmentioning
confidence: 56%
“…DinB synthesizes DNA up to and across from tC, accurately incorporating G, but cannot efficiently bypass tC. It has also been observed that tC can tautomerize to a form that base pairs with A; 41,42 however, similar to human DNA primase and RNA polymerase, 42,43 we did not observe misincorporation by DinB. The tC analog is known to be bypassed by the A-family polymerase Klenow fragment, as well as by human DNA polymerase α primase.…”
Section: Discussionmentioning
confidence: 56%
“…Using a similar strategy, post-transcriptional fluorescent labeling of the pRNA molecule was readily achieved using functionalized fluorophores, harboring a mono-alkylating reactive group, developed by Mirus (Label IT labeling reagent, Mirus). More recently, it was demonstrated that T7 RNA polymerase can be used for in vitro enzymatic fluorescent labeling of the RNA molecule using the new reagent tCTP[76]. Different T7 RNA polymerase mutants were constructed to recognize and permit the incorporation of 2′-modified triphosphate ribonucleotide such as 2′-Ome, 2′-F, 2′-NH 2 , 2′-N 3 into the RNA chain[7780].…”
Section: Bottom-up Assembly Of Prna Nanoparticlesmentioning
confidence: 99%
“…�owever, the primary difficulty with hydrogen-bonded unnatural base pairs is the instability of the hydrogen-bonding geometry due to tautomerization [32]. Indeed, the tautomeric equilibrium is a general feature of hydrogen-bonded base analogs [33,34].…”
Section: Creation Of Unnatural Base Pairs For Pcr Amplificationmentioning
confidence: 99%